Methodology for Structural Analysis of Polysaccharides - Guo, Qingbin (Biobased Polymers,, 2018)
Written by an academic and industry insider, this book provides an informed study on polysaccharide structural analysis and characterization. Specifically focused on analytical techniques, methodologies, and interpretation of data, featured topics include: monosaccharide composition; methylation analysis; 1D & 2D NMR (Nuclear Magnetic Resonance) and MALDI-TOF- (MS) Mas spectrometry. This book is aimed at advanced undergraduates, academic and industrial researchers and professionals studying or using biobased polymers.